2022
DOI: 10.1177/08987564221076908
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Furcation Lesions in Dogs – A Review

Abstract: The furcation is the anatomic area where the roots divide on a multirooted tooth. Periodontal disease causing alveolar bone loss can lead to furcation lesions of various stages. Once furcation involvement has occurred, the area can be more difficult to clean or treat due to the complex anatomy and morphology of furcations. Teeth with short root trunks, longer tooth roots, and roots with wide furcation entrance areas/degrees of separation and wide root divergence are considered better candidates for long term m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 136 publications
(471 reference statements)
0
4
0
Order By: Relevance
“…This is not surprising, as again, with fewer walls, there is decreased stability of the bone graft to maintain space for clot stabilization and support the overlying barrier membrane without displacement. Zacher and Marretta ( 23 ) recently provided a comprehensive review of furcation lesions, including emphasizing characteristics of teeth with furcation lesions that are favorable for maintaining those teeth in the oral cavity. In the context of GTR, a wide furcation entrance area with wide root divergence may be favorable because these characteristics facilitate detection and access for treatment of furcation defects ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising, as again, with fewer walls, there is decreased stability of the bone graft to maintain space for clot stabilization and support the overlying barrier membrane without displacement. Zacher and Marretta ( 23 ) recently provided a comprehensive review of furcation lesions, including emphasizing characteristics of teeth with furcation lesions that are favorable for maintaining those teeth in the oral cavity. In the context of GTR, a wide furcation entrance area with wide root divergence may be favorable because these characteristics facilitate detection and access for treatment of furcation defects ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zacher and Marretta ( 23 ) recently provided a comprehensive review of furcation lesions, including emphasizing characteristics of teeth with furcation lesions that are favorable for maintaining those teeth in the oral cavity. In the context of GTR, a wide furcation entrance area with wide root divergence may be favorable because these characteristics facilitate detection and access for treatment of furcation defects ( 23 ). The current study confirmed that GTR in F3 lesions is highly likely to fail.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the severity of the pathological picture, each subject was assigned an increasing score, corresponding to a mild, intermediate, or advanced stage of periodontal disease. For classification of patients, the authors considered the gingival disease index [33] and the stages of furcation involvement and exposure index [34].…”
Section: Patient Preparation and Samplingmentioning
confidence: 99%
“…9,10 Older literature recommended the removal of cementum to smooth the tooth surface, however, current recommendations are to minimize the removal of this important normal tooth structure. 11,12 Two ways by which the periodontium heals diseased tissue are regeneration and repair. Regeneration is the restoration of normal anatomy.…”
Section: Introductionmentioning
confidence: 99%